(untitled) (Research, Society and Development, 2021)
The occupation and alteration of watercourses is a process observed in several Brazilian municipalities. This fact often occurs, due to the lack of planning in cities, and the mismatch between the urbanization process, and the legislation. In the understudy hydrographic sub-basin, there are intensely anthropogenic stretches, with the channeled water bodies alternating with open stretches. However, there are also stretches inserted in areas of a massive forest. Thus, this study aimed to evaluate and diagnose the projection areas of the Permanent Preservation Areas - APP strips in the Pedro Lessa Sub-basin, and thus discuss the feasibility of applying the sanitary range established in municipal legislation (Complementary Law No. 551/2019) given the Brazilian Forest Law (Federal Law No. 12.651/2012). For that, a socio-environmental technical study methodology was used, with the survey of geoprocessing data and on-site inspections. From the data, an impact analysis was carried out, applying an impact matrix, in which current and hypothetical scenarios were simulated with certain criteria, to know the positive and negative scores of each scenario. From the data and results obtained, it is possible to observe the irreversibility of the recovery of the marginal strip of watercourses in areas already occupied, making the application of the sanitary strip viable. Also, it was observed the importance of maintaining the areas of massive forests, with the application of the forest law.